Consequências Políticas da Empolgação Comercial [Karl Marx] - Marx, Karl (Revista de Ciências do Estado, 2017)
Tradução de MARX, Karl. Political Consequences of the Commercial Excitement. In: Collected Works, v. 11. Nova York: Lawrence & Wishart, 1980, pp. 364 –368